2021
DOI: 10.35812/cellulosechemtechnol.2021.55.71
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co2-Added Steam Explosion on Oil Palm Empty Fruit Bunch for Bioethanol Production

Abstract: This study aimed to investigate the effect of adding CO2 as an impregnation agent in steam explosion on oil palm empty fruit bunch (EFB) for bioethanol production. The influence of this treatment on the characteristics of EFB, enzymatic hydrolysis, and fermentation of EFB was evaluated in this investigation. CO2-added steam explosion was conducted varying the CO2 impregnation time (0, 30, 60 min). The results showed that the addition of CO2 in steam explosion increased the surface area, pore area, and pore vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It indicated that some silica was removed from OPEFB. The pretreatment can reduce lignin content and remove the biomass's silica [43]. According to Fig.…”
Section: Influence Of Three-constituent Des On Delignification and Fu...mentioning
confidence: 99%
“…It indicated that some silica was removed from OPEFB. The pretreatment can reduce lignin content and remove the biomass's silica [43]. According to Fig.…”
Section: Influence Of Three-constituent Des On Delignification and Fu...mentioning
confidence: 99%
“…32 Alternative to bio-oil integration potential, the blending of bio-ethanol (derived from biomass fermentation) with petroleum fuel (e.g., gasoline, diesel, and jet fuel) is another promising integration pathway to establishing a CE relationship between the agriculture and petroleum industry. 33 Prior to the fermentation process, pre-treatment processes (e.g., acid treatment, 34 alkali treatment, 35 sequential acid and alkali treatment, 36 and steam and CO 2 explosion treatment 37 ) are essentially needed to increase the cellulose concentration in the substrate from the breakdown of complex hemicellulose and lignin structures. It is followed by enzymatic hydrolysis or saccharification to cleave the large cellulose molecules into monosaccharide sugars to promote ethanol production during fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the fermentation process, pre-treatment processes ( e.g. , acid treatment, alkali treatment, sequential acid and alkali treatment, and steam and CO 2 explosion treatment) are essentially needed to increase the cellulose concentration in the substrate from the breakdown of complex hemicellulose and lignin structures. It is followed by enzymatic hydrolysis or saccharification to cleave the large cellulose molecules into monosaccharide sugars to promote ethanol production during fermentation .…”
Section: Introductionmentioning
confidence: 99%